Pengaruh Ukuran Partikel, Perbandingan Jumlah Pelarut dan Waktu Maserasi terhadap Perolehan Rendemen Aquilaria Malaccensis Lam. - Miftahurrahmah Miftahurrahmah; Hasnah Ulia; Harmiwati N. H (Politeknik ATI Padang, 2021)
Aquilaria Malaccensis Lam. is one of the most popular plants contains essential oil, both of them used by pharmaceutical and also cosmetic industry. The plants used in this study came from Jambi, Indonesia which is known, It’s one of the best quality agarwood in the world. This study aims to determine the best conditions for the yield so that it can be produced on an industrial scale. The study reviewed the effect of yield based on size of particles, ratio of solvent, and the operating time, maceration. The research was carried out in three steps. The first, raw material preparation, fermentation and maceration, and then evaporation. Preparation of raw materials is prepared in three variables, 2-5 cm, ±2cm, and size <40 mesh. Methanol is the solvent that will be used in multiple ratio of solvent to agarwood, its 1:7, 1:9, and 1:11(gr/ml). In addition, the maceration time was varied for each sample, 1 day, 2 days, and 3 days. Based on the research variables, obtained essential oil of agarwood dark brown in colour, with a special fragrance of agarwood. Based on the difference in particle size, it is known that size <40 mesh, yield is 3.16%, while for the larger size, 2-5 cm, the yield is 3.12%. In the variable ratio of the amount of solvent used, it is known that 1:9 (gr/ml) is the best point for yield. At maceration step known that 2-3 days, it doesn’t gives a significant change, 2.12 g for 3 days, and 1.92 g for 2 days.